Management of acute basilar artery occlusion: Should any treatment strategy prevail? - Dornak, Tomas; Herzig, Roman; Sanak, Daniel; Skoloudik, David (Biomedical papers, 2014)
Background: Acute basilar artery occlusion (BAO) is relatively infrequent form of acute ischemic stroke associated with severe and persisting neurological deficit and high mortality rate (to 86%). Early recanalization is essential for good clinical outcome but the most effective treatment approach remains unestablished. Several treatment strategies are currently available but their safety and efficacy have only been tested in retrospective/prospective case series. Randomized controlled trials (RCTs) are lacking.Methods and Results: We searched the PubMed database for assessments of recanalization rate and clinical outcome in BAO patients treated with various treatment methods. The results show that antithrombotics are least effective while specific reperfusion therapies including intravenous thrombolysis (IVT) and various types of intra-arterial therapy (IAT) are more so. Less than half of BAO patients reach independent outcome following IVT with a recanalization rate 52 - 78%. Even though IAT recanalizes BAO more frequently (in up to 100%), the higher recanalization rate is not necessarily associated with better outcome.Conclusions: Good clinical outcome is strongly dependent on recanalization time. Thus, the concept of bridging therapy, combining widely available IVT with IAT, was introduced and is usually considered a rescue strategy in non-responders to IV alteplase. A trend to better outcome in patients treated with bridging therapy in some studies, has to be confirmed by large RCTs.
Keywords: ischemic stroke; basilar artery; occlusion; treatment method; recanalization; outcome